Hukum Tanah dan Kewarganegaraan dalam Perkawinan Silang di Indonesia - Naila Nurazizah; Ahmad Ashfannawa Fauza; Ismi Arinal Mufidati (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Cross-national marriages between Indonesian citizens and foreign nationals generate complex legal issues concerning land ownership and citizenship. The Basic Agrarian Law (UUPA) and Citizenship Law No. 12 of 2006 have yet to harmonize their provisions regarding property rights within mixed-nationality marriages. This study aims to analyze the interrelation between land law and citizenship in cross-national marriages and evaluate their legal certainty. The research employs a normative-empirical approach by reviewing statutory regulations, case law, and interviews with land officials. The findings reveal a normative conflict between the prohibition of land ownership by foreign nationals and the constitutional right of Indonesian citizens married to foreigners to acquire joint property rights. Such disharmony leads to legal uncertainty and potential violations of property rights. The study concludes that reforming Indonesia’s land and citizenship law is crucial to accommodate international marriage dynamics and ensure legal certainty for all citizens.